1992
DOI: 10.1063/1.107488
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue and retention in ferroelectric Y-Ba-Cu-O/Pb-Zr-Ti-O/Y-Ba-Cu-O heterostructures

Abstract: Fatigue and retention characteristics of ferroelectric lead zirconate titanate thin films grown with Y-Ba-Cu-O(YBCO) thin-film top and bottom electrodes are found to be far superior to those obtained with conventional Pt top electrodes. The heterostructures reported here have been grown in situ by pulsed laser deposition on yttria-stabilized ZrO2 buffer [100] Si and on [001] LaAlO3. Both the a- and c-axis orientations of the YBCO lattice have been used as electrodes. They were prepared using suitable changes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
77
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 364 publications
(78 citation statements)
references
References 19 publications
1
77
0
Order By: Relevance
“…[3][4][5] In particular, Pb(Zr 0.52 Ti 0.48 )O 3 with a low coercive field and high remnant polarization 6 has been widely investigated for application in microwave devices, 7 energy storage, and capacitance. 8 However, the common Pb loss induced a large number of oxygen vacancies, which locate typically at grain boundaries or/and at the interfaces between PZT and electrodes.…”
mentioning
confidence: 99%
“…[3][4][5] In particular, Pb(Zr 0.52 Ti 0.48 )O 3 with a low coercive field and high remnant polarization 6 has been widely investigated for application in microwave devices, 7 energy storage, and capacitance. 8 However, the common Pb loss induced a large number of oxygen vacancies, which locate typically at grain boundaries or/and at the interfaces between PZT and electrodes.…”
mentioning
confidence: 99%
“…It has been reported that the PZT ferroelectric thin films with conducting YBCO oxide electrode yield better fatigue characteristics than those with Pt electrodes [8]. In this paper, the ferroelectric properties as well as the superconducting properties for the PZT/YBCO/MgO film are studied.…”
Section: Resultsmentioning
confidence: 99%
“…Several metal/metal oxide structures are being investigated to find a suitable electrode/diffusion barrier combination with low resistivity, good adhesion, excellent diffusion barrier properties, good thermal stability, and high chemical corrosion resistance. 1,[3][4][5][6] However, these electrode or electrode/barrier materials are reported to be stable up to 700°C which is lower than the commonly reported processing temperature of SBT ͑750-800°C͒ and, for that reason, fewer studies have been focused on the effects of electrode/diffusion barrier materials on the properties of SBT thin films for the realization of highdensity memories. 7 In this letter, we report on the properties of a low temperature processed 0.7SrBi 2 Ta 2 O 9 -0.3Bi 3 TaTiO 9 ͑0.7SBT-0.3BTT͒ solid-solution thin films fabricated directly on n ϩ -polycrystalline (n ϩ -poly͒ Si substrates with Pt-Rh ͑10% Rh͒ and Pt-Rh-O x as the electrode and diffusion barrier layers, respectively.…”
Section: ͓S0003-6951͑99͒01240-1͔mentioning
confidence: 99%